Dr. Peymaneh Amini — Deep Plane Facelift — Bad Homburg - Amini, Peymaneh (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Peymaneh Amini, practicing in Bad Homburg, Germany. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003207; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; germany; bad homburg